Telephone survey of inguinal hernia repair patients older than 5 years for chronic pain - Embleton, Didem Baskın; Tuncer, Ahmet A.; Çetinkurşun, Salih (International Surgery Journal, 2018)
Background: Little is known about chronic pain in the inguinal region following inguinal hernia repair in children. A study was conducted to examine whether pain is an important complication of inguinal hernia surgery in children. Methods: A telephone survey was performed of former patients who had undergone inguinal hernia repair and are now older than 5 years. A questionnaire was prepared and the questions were asked by paediatric surgeons. Results: There were 66 former patients now older than 5 years old. Patients had inguinal hernia repair at between 11 days and 14 years of age (mean 3.24 years). Age during telephone survey was between 5 and 18 years (mean 7.48 years). One patient had late pain related to direct inguinal hernia occurrence (1.5%). Three patients described non-specific abdominal pain unrelated to the inguinal operation. None of the patients were taking painkillers. Conclusions: Although this is a small sample group, chronic pain does not seem to be a serious problem after inguinal hernia repair in children.